E Effect Of Leadership and Work Motivation on Employee Performance Through Knowledge Sharing Behavior: Effect Of Leadership and Work Motivation on Employee Performance Through Knowledge Sharing Behavior - Inang, Nur Iman (Archives of Business Research, 2021)
This study explains the influence of leadership and work motivation on employee performance at private universities (PTS) within the province of Southeast Sulawesi which is mediated by knowledge-sharing behavior. Research method uses a survey approach and explanatory research. The sampling technique is probability sampling with the unit of analysis, namely the employees of private universities (PTS). Data analysis was conducted to test the hypothesis by using PLS software. Results show that leadership has a positive and significant effect on knowledge sharing behavior and employee performance. Work motivation has a significant positive effect on knowledge sharing behavior and employee performance. Knowledge sharing behavior has a positive effect on employee performance. Finally, research can prove that leadership and work motivation together have a positive and significant effect on employee performance and knowledge sharing behavior acts as a mediation of the relationship between leadership and work motivation with employee performance.